Numerical study on failure process of aluminium plate subjected to normal impact by hemispherical projectiles - Ibrahim, Mohd Norihan; Adi Siswanto, Waluyo; Ahmad Zaidi, Ahmad Mujahid (Trans Tech Publication Ltd, 2014)
In this paper a study is presented on the numerical analysis of the failure process of aluminium armour plate subjected to normal impact by hemispherical projectiles. The perforation process has been simulated by the application of 3D analysis using IMPACT dynamic FE program suite. The comparison on the elements size of meshing towards failure mode was observed and evaluated. The material behaviour of the target plate was approximated by an appropriate constitutive relation. The study covered different size of meshing element on target plate as well as different level of impact velocities. Different failure modes for each case were found. For low speed impact condition a petalling was observed, whereas for high speed impact a radial neck along with a holes enlargement was observed with better and uniform perforation mode. The deformation and failure mode of the impacted target plate will be given special attention in this investigation.